ADMINISTRATIVE AND LEGAL REGULATION OF SOCIAL PROTECTION OF MILITARY PERSONNEL AND THEIR FAMILIES: SWISS MODEL - Petkov, Sergey; Makarova, Tetiana (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . The relevance of studying the experience of administrative and legal regulation of social protection of military personnel in the leading democratic countries of the world is of great importance for its consideration and implementation in the period of formation of modern social rights of military personnel and members of their families in the context of a full-scale war in Ukraine. This paper examines the Swiss model of military service, which is based on the absolute unity of the people and the army, the citizen and the State, and the purposeful work of the administrative and legal mechanism for the comprehensive protection of human rights, including those of military personnel. The purpose of the article is to study the experience of leading democratic countries, in particular, the Swiss model of military service, with a view to creating a modern administrative and legal regulation of social protection of military personnel and their families in the context of a full-scale war in Ukraine, and to formulate practical proposals for the introduction of a fair and transparent mechanism of social guarantees for military personnel and their families based on the national traditions of the Cossacks and democratic achievements.M e t h o d s . The research was conducted using general scientific methods of analysis, synthesis and formal legal method. The use of the above methodological tools made it possible to analyze and highlight the information from the sources and legal acts, to clarify the content of the legal provisions of these acts and to obtain new knowledge reflected in the material presented.R e s u l t s . The analysis resulted in the identification of information on the administrative and legal regulation of social protection of military personnel and their families in the Swiss model of military service, which is based on the police principle, as well as the issue of fulfillment of civil duty by members of Swiss society regarding compulsory military service, the basis of which is a comprehensive, fair and understandable mechanism of administrative and legal support by the state for the social rights of military personnel.C o n c l u s i o n s . Several conclusions and proposals aimed at improving the regulation of administrative and legal support for the social rights of military personnel and their families in Ukraine have been developed. In the context of a full-scale war, Ukraine needs to create an army that will become an integral and essential part of Ukrainian society.